The year 2017: Megafires and management in the cerrado - Fidelis, Alessandra [UNESP]; Alvarado, Swanni T. [UNESP]; Barradas, Ana Carolina S.; Pivello, Vânia R. (MDPI, 2018)
The year 2017 was a megafire year, when huge areas burned on different continents. In Brazil, a great extension of the Cerrado burned, raising once more the discussion about the “zero-fire” policy. Indeed, most protected areas of the Cerrado adopted a policy of fire exclusion and prevention, leading to periodic megafire events. Last year, 78% of the Chapada dos Veadeiros National Park burned at the end of the dry season, attracting media attention. Furthermore, 85% of the Reserva Natural Serra do Tombador burned as a result of a large accumulation of fuel caused by the zero-fire policy. In 2014, some protected areas started to implement the Integrate Fire Management (IFM) strategy. During 2017, in contrast to other protected areas, the Estação Ecológica Serra Geral do Tocantins experienced no megafire events, suggesting that a few years of IFM implementation led to changes in its fire regime. Therefore, we intended here to compare the total burned area and number of fire scars between the protected areas where IFM was implemented and those where fire exclusion is the adopted policy. The use of fire as a management tool aimed at wildfire prevention and biodiversity preservation should be reconsidered by local managers and environmental authorities for most Cerrado protected areas, especially those where open savanna physiognomies prevail. Changing the paradigm is a hard task, but last year’s events showed the zero-fire policy would bring more damage than benefits to Cerrado protected areas.
Keywords: Altered fire regime; Fire incidence; Fire risk; Fuel load; Integrated Fire Management; Megafires; Protected areas; Tropical savanna